Оцінка роботи служби передрейсового обслуговування автобусів - Форнальчик, Євген; Виджак, Мар’яна (Видавництво Львівської політехніки, 2018)
Collected and processed the results of expert polls drivers and technical workers of the enterprise in terms of completeness of the operations taking the bus service and technical support.
Assessment of the completeness of the performance taking bus service
Keywords: 656.13